A novel fusion levansucrase improves thermostability of polymerization and production of high molecular weight levan. (October 2021) - Zhang, Xi; Liang, Yuezhao; Yang, Haibo; Yang, Hui; Chen, Shuochang; Huang, Fei; Hou, Yuanyuan; Huang, Ribo
Abstract: A novel fusion levansucrase (TPS-SacB-T305A) was constructed by adding to SacB-T305A an extra C-terminus of the trehalose-6-phosphate synthase (TPS) involved in its thermostability. The fusion TPS-SacB-T305A was expressed in Escherichia coli and purified, its hydrolytic V max and K m were about 39.53 μmol/(minute*mg protein) and 13.36 mmol/L, respectively. The levan production reached 71.6 ± 2.06 g/L with a conversion yield of 35.8 ± 1.03% using sucrose as substrates under the present optimum condition of polymerization and the products were characterized by NMR and FT-IR. Interestingly, the optimum temperature of fused TPS-SacB-T305A was 15 °C higher than that of free SacB-T305A on levan polymerization, and the half-life at 40 °C of fusion enzyme increased to more than 4-fold. The proportion of high molecular weight (HMW) levan (approximately 2000 kDa) to total polysaccharides was raised tremendously from approximately 4% (catalyzed by free SacB-T305A) to approximately 91% (catalyzed by TPS-SacB-T305A). The present study provides a potential industrial enzyme to produce HMW levan and helps to explore the mechanism of levan polymerization. Graphical abstract: Image 1 Highlights: Constructed a thermostable fusion enzyme for high molecular weight (HMW) levan production. Half-life for polymerization at 40 °C of fusion enzyme increased to more than 4-fold. The optimum polymerization temperature of fusion enzyme reached 45 °C. The conversion yield of sucrose to levan reached 35.8 ± 1.03%. Increased the proportion of HMW levan to total products from approximately 4%–91%.